1999
DOI: 10.1152/ajpheart.1999.277.1.h399
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-induced endothelin release and vasoreactivity in hypertriglyceridemic and hypertensive rats

Abstract: Insulin-elicited endothelin release in hypertriglyceridemic, hypertensive, hyperinsulinemic (HTG) rats was shown. Weanling male Wistar rats were given 30% sucrose in their drinking water for 20–24 wk. In vitro contractions of aorta and femoral arteries were elicited with 40 mM KCl. Endothelin release induced with KCl plus 50 μU/ml insulin resulted in increases in contractile responses: 41 ± 5.9 and 57 ± 6% for control and 65.5 ± 6 and 95 ± 9% for HTG aortas and femoral arteries, respectively. The endothelin ET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…But after the HTG rats drink the 30% sucrose solution, their levels of insulin may increase significantly. With reference to this we have shown that even a moderate insulin increase can induce in vitro endothelin release in rat aorta and femoral arteries (25), an effect that could extend to HTG coronary vessels and modify their function.…”
Section: General Characteristicsmentioning
confidence: 70%
“…But after the HTG rats drink the 30% sucrose solution, their levels of insulin may increase significantly. With reference to this we have shown that even a moderate insulin increase can induce in vitro endothelin release in rat aorta and femoral arteries (25), an effect that could extend to HTG coronary vessels and modify their function.…”
Section: General Characteristicsmentioning
confidence: 70%
“…It has been suggested that the imbalance between vasoconstriction and vasodilatation and the development of high SBP and MS may be partly due to an increase in vasoconstrictors dependent on the sympathetic system, as well as a deficiency in the expression of eNOS and in the antioxidant system [11,12,29].…”
Section: Discussionmentioning
confidence: 99%
“…At the end of each week, during glycine treatment, systolic arterial BP was measured by connecting the tail cuff to a pneumatic pulse transducer and a programmed electrosphygmomanometer (Narco Biosystems) as described previously (39). Recordings were made in triplicate by means of a Grass polygraph (Grass Medical Instruments, Quincy, MA).…”
Section: Methodsmentioning
confidence: 99%